COMPARISON OF %PRO2 PSA AND PROSTATE HEALTH INDEX FOR DETECTION OF PROSTATE CANCER, A SINGLE CENTER STUDY. WHO IS A BETTER PREDICTOR? - Krstev, Toni; Stojanoski, Ivica; Oranska, Gordana; Trpkovska, Biljana; Karce, Ateme (Journal of Morphological Sciences, 2024)
Measurement of serum prostate-specific antigen (PSA) for the detection of prostate cancer has poor specificity in men with PSA levels between 4 and 10 ng/ml. It has been suggested that measurement of the pro2PSA, %pro2PSA and PHI might offer an improvement. We performed a systematic review and meta-analysis to evaluate the diagnostic presentation of these tests among men with PSA levels between 4 and 10 ng/ml in the „gray zone“.   We examined 100 men age 50 years or older with prostate specific antigen 4 to 10 ng/ml  in the „gray zone“ and normal digital rectal examination with suspected prostate cancer who had undergone biopsies and were divided into a benign and malignant group.  In this population we compared the performance of prostate specific antigen (PSA), %p2PSA and PHI to predict prostate cancer and specifically, the presence of clinically significant prostate cancer (csPCa) using multiple criteria.We found statistically significantly increased levels of %pro2PSA, and PHI compared to PSA in patients diagnosed with prostate cancer by prostate biopsy vs. patients with benign prostatic conditions . Conclusions: Both PHI and %p2PSA significantly increased the diagnostic accuracy than PSA as a biomarker. But, PHI is a slightly better predictor in comparison to %p2PSA for the identification of clinically significant prostate cancer and may help to reduce unnecessary prostate biopsies. Keywords :  PHI; %p2PSA, prostate cancer, identification of csPCa, prostate biopsy